L.A. confidential - Ellroy, James, 1948- (Grand Central Publishing : Sold by Hachette Book Group, 2013)
Three troubled cops-- Ed Exley, desperately seeking glory; vengeful Bud White, a witness to his mother's murder by his father; and Jack Vincennes, a shakedown artist with a dark secret-- tread a fine line between right and wrong in 1950s Los Angeles.